2023
DOI: 10.3390/app13127291
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility in Radiomics: A Comparison of Feature Extraction Methods and Two Independent Datasets

Abstract: Radiomics involves the extraction of information from medical images that are not visible to the human eye. There is evidence that these features can be used for treatment stratification and outcome prediction. However, there is much discussion about the reproducibility of results between different studies. This paper studies the reproducibility of CT texture features used in radiomics, comparing two feature extraction implementations, namely the MATLAB toolkit and Pyradiomics, when applied to independent data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…There is a need for larger independent datasets to test models. The reproducibility of radiomics features and their relationship to biomedicine needs further study [ 38 ], and it is important that methodologies are reported in sufficient detail to enable others to reproduce results [ 39 ].…”
Section: Radiomics Applicationsmentioning
confidence: 99%
“…There is a need for larger independent datasets to test models. The reproducibility of radiomics features and their relationship to biomedicine needs further study [ 38 ], and it is important that methodologies are reported in sufficient detail to enable others to reproduce results [ 39 ].…”
Section: Radiomics Applicationsmentioning
confidence: 99%